DIVERSITY OF GYMNOSPERMS IN THE LANDSCAPING OF THE HOLY SPIRIT CATHEDRAL IN CHERNIVTSI - Honcharenko, Yanina; Sokolenko, Uliana; Oleksiichenko, Nadiia; Podolkhova, Marianna (Theory and practice of design, 2025)
The article presents the results of landscaping studies conducted on the territory of the Holy Spirit Cathedral in Chernivtsi and the analysis of the range of Gymnosperms. Thirty species and cultivars of ornamental coniferous plants were identified on the cathedral grounds, which are absent in other garden and park of the city. The analysis of the correspondence between the decorative qualities of the existing plants and the recommendations on sacred symbolism shows that the latter is not fully observed. Given the important functions of sacred structures as centers of psychological rehabilitation, tourist attraction, and image enhancement of the city, it is recommended to select plants and design compositions based on scientifically grounded landscaping projects. The purpose of the research is to analyze the diversity of Gymnosperms on the territory of the Holy Spirit Cathedral in Chernivtsi to determine the potential of the most valuable ornamental species for further introduction into urban green infrastructure and to increase their aesthetic appeal. The research methodology is based on the analysis of literary sources and the study of existing examples of landscaping sacred sites in Ukraine and abroad. Route and field surveys, as well as methods of analysis and comparison, were applied. The results of the study indicate that the selection of plant assortments for landscaping sacred sites remains a debatable issue due to the absence of clear guidelines. The modern range of nurseries makes it possible to use plants with diverse decorative characteristics. However, the lack of a scientifically based landscaping project may lead to the planting of species that do not meet environmental requirements, which in turn causes deterioration of their sanitary condition and loss of decorativeness. The presence of well-adapted, highly ornamental coniferous cultivars on the cathedral territory, which are absent in the parks and squares of Chernivtsi, provides grounds for enriching the diversity of gymnosperms in various types of urban plantings. Sacred territories can additionally perform functions of rehabilitation centers, improve the psycho-emotional state of visitors, and contribute to tourism development. The scientific novelty lies in identifying the range of ornamental coniferous plants on the territory of the Holy Spirit Cathedral in Chernivtsi, analyzing their symbolic meaning, and determining their compliance with the sacred character of the site. The introduction of the most adapted species into urban green spaces will expand the diversity of ornamental plants, enhance the aesthetic appeal of the city’s architectural landscape, and consequently strengthen the image of Chernivtsi as a tourist destination. Practical relevance. The identified ornamental plants can serve as positive examples of species selection and contribute to their wider use in urban parks and squares. The revealed shortcomings in the existing landscape compositions highlight the need to develop a comprehensive landscaping project that considers ecological characteristics of plants. The landscaped areas of sacred buildings can provide mul- tiple ecosystem services, primarily cultural ones.